Effects Of Phototherapy On Serum Calcium Level In Neonates With Hyperbilirubinemia - Qura-tul-Ain Javaid; Salma Aziz; Noor-ul-Ain; Uzma Abid; Ayesha Afzal; Umer Javaid (Journal of Rawalpindi Medical College)
Objective: To study the frequency of hypocalcemia in neonates receiving phototherapy with indirect hyperbilirubinemia Materials and Methods: Descriptive case series study was conducted from September 5, 2018, to March 5, 2019, in the NICU of the Paediatric Department Benazir Bhutto Hospital, Rawalpindi.